Mobilizing Private Climate Financing in Emerging Market and Developing Economies - Prasad, Ananthakrishnan (Staff Climate Notes; Staff Climate Note, 2022)
Global investment to achieve the Paris Agreement's temperature and adaptation goals requires immediate actions-first and foremost-on climate policies. Policies should be accompanied by commensurate financing flows to close the large financing gap globally, and in emerging market and developing economies (EMDEs) in particular. This note discusses potential ways to mobilize domestic and foreign private sector capital in climate finance, as a complement to climate-related policies, by mitigating relevant risks and constraints through public-private partnerships involving multilateral, regional, and national development banks. It also overviews the role the IMF can play in the process.